Editor’s introduction to the Guest Editor Pamela Wible - Mariaelena Bartesaghi (Qualitative Research in Medicine & Healthcare)
I want to thank Dr. Wible for agreeing to act as guest editor of this issue. Dr. Pamela Wible is a family physician born into a family of physicians who warned her not to pursue medicine. She soon discovered why - to heal her patients she first had to heal her profession. (...)